Key competencies among engineering leaders in the Malaysian construction industry - Alim Maktar; Khairun Nisa Khairuddin; Ummi Naiemah Saraih (Penerbit Universiti Kebangsaan Malaysia, 2024)
In the rapidly evolving field of engineering, effective leadership is essential for the successful completion of complex projects. However, engineers often hesitate to take on leadership roles and are underrepresented in leadership positions. While there is a growing body of literature on engineering leadership, much of it lacks empirical rigor and tends to focus on managing engineers rather than leadership competencies. Moreover, research specific to engineering leadership, particularly in Malaysia, is limited. This study addresses these gaps by exploring the key competencies required for engineering leaders in Malaysia’s construction industry. Using a qualitative research design, data was collected through in-depth interviews with 17 engineering leaders. Purposive sampling was employed to select participants based on specific criteria. Constant comparative analysis revealed three primary competencies: (1) the ability to establish and work toward a set vision, (2) the ability to frame and address engineering project issues, and (3) the ability to manage resources effectively. This study contributes valuable insights into the competencies that define effective engineering leaders, offering practical implications for leadership development and engineering management practices. By cultivating these competencies, organizations can enhance leadership capabilities and improve project outcomes. The findings suggest that focusing on strategic vision, problem-solving, and resource management can help foster better leadership in engineering projects. Ultimately, this research lays the foundation for further exploration into engineering leadership, particularly in non-Western contexts, and provides a model for leadership development tailored to the engineering domain.